1999
DOI: 10.1186/ar9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The genetic basis for rheumatoid arthritis (RA) is likely to be extremely complex. Even the role of MHC genes remains to be fully defined, and may involve interactive genetic effects. The difficulty of precisely defining the clinical phenotype, as well as underlying genetic heterogeneity, complicates the problem. In addition, stochastic genetic or physiologic events may contribute to the low penetrance of susceptibility genes. This situation parallels developing paradigms for other autoimmune disorders, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(7 citation statements)
references
References 71 publications
1
5
0
1
Order By: Relevance
“…Consistent with the results of previous studies, our study indicates that RA is a disease involving a complex gene network and multiple gene contributors [ 28 ]. In this study, 39 genes were selected in the PPI network and 9 hub genes were identified after modular analysis of the PPI network, including CFL1, COTL1, ACTG1, PFN1, LCP1, LCK, HLA-E, FYN, and HLA-DRA.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results of previous studies, our study indicates that RA is a disease involving a complex gene network and multiple gene contributors [ 28 ]. In this study, 39 genes were selected in the PPI network and 9 hub genes were identified after modular analysis of the PPI network, including CFL1, COTL1, ACTG1, PFN1, LCP1, LCK, HLA-E, FYN, and HLA-DRA.…”
Section: Discussionsupporting
confidence: 93%
“…Like other autoimmune diseases, RA has a strong genetic component with a heritability of ~60% based on twin data (1–3). To elucidate the genetic and molecular basis of RA, tremendous efforts have been made in the mapping of quantitative trait loci (QTL) associated with the disease.…”
mentioning
confidence: 99%
“…Citrullination [ 19 ] leads to the activation of complex immune responses and specific ACPA generation, found in approximately 75% of RA patients [ 20 ]. The risk of developing RA also depends on hereditary factors [ 21 ], and over 100 genetic loci are involved in an increased risk of RA [ 22 ]. Interestingly, twin studies have found no difference in heritability in subsets of ACPA-positive and ACPA-negative RA [ 23 ].…”
Section: Role Of Autoantibodies In Predicting the Response To Ra Tmentioning
confidence: 99%